Illustrator 2020 Essential Training. - Harmer, Tony (linkedin.com, 2019)
Learn the essentials of Adobe Illustrator. Find out how to use the 2020 version of Illustrator to create amazing artwork—from minimalistic logos to full-blown illustrations.